Evaluation of DLL3 Expression in Small Cell Lung Carcinoma in Southern Brazil and its Correlation with EGFR, PDL-1, CICLIN D 1, Neuroendocrine Markers and Clinical Findings - Barcelos Marçal, Josenel Maria; Bonato, Giuseppe Dick; Iaroseski, Júlia; Baptistela, Caroline; Ribeiro da Rosa, Janaina; Machado Rosa, Rafael Fabiano; Gazzola Zen, Paulo Ricardo (International Journal of Innovative Research in Medical Science, 2021)
Small cell lung carcinoma (SCSL) is a rare malignancy whose treatment is palliative. The knowledge of its biology is important for the development of new therapies. The expression of delta like 3 protein (DLL3) is involved in the regulation tumorigenic in SCSL. The aim of this study was to evaluate the expression of DLL3 in small cells lung carcinoma (SCLC) and its correlation with clinical data, survival and association with other biomarkers. Methods: a cohort retrospective of 56 patients from institution in Southern Brazil was analyzed. The expression of DLL3 was positive when present in 5% or more of the membranes and cytoplasm of neoplastic cells. PDL -1 and EGFR were positive when expressed in 1% or more of the membranes, ciclin D1 and KI 67 by the percentage of stained nucleus. Synaptophysin, chromogranin and CD56 were tabulated with 1 positive and zero for negative. DLL 3 expression was evaluated as mean, standard deviation and quartiles. Clinical-demographic and death data were analyzed using Fisher's exact test and Pearson's test. Cox regression and the Kaplan-Meier curve were used for survival. Results: Of 56 individuals, 16 were excluded because there was no tumor available and 13 patients (32.5%) had positive DLL 3. EGFR expression was 46.2% (HR 2.4), PDL-1 30.8% (HR 3.56) cyclin D1 53.8% (HR 2.77) and chromogranin A 30.8% (HR 0.3) All patients positive for chromogranin A were negative for anti-DLL3 (p> 0.17). The overall survival for positive DLL3 was slightly higher (p = 0.711) as well as for chromogranin A negative (p 0.299) Conclusion: The DLL3 mutation acts on SCLC tumorigenesis. The study of its expression may be useful for the development of new therapies. The inverse correlation between DLL3 and chromogranin .A may represented a protective factor, but it needs to be better studied in a larger cohort.